2018
DOI: 10.2486/indhealth.2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Identifying shift worker chronotype: implications for health

Abstract: Shift workers are at risk for developing serious health issues due to short sleep. One cause of short sleep is circadian misalignment: sleep time is not synchronized with the body’s natural circadian rhythms. Although circadian rhythms are strongly driven by the light/dark cycle, humans have individualized sleep time preferences (chronotypes) based on genetics, development, and external influences. Evening chronotype individuals fall asleep later than average and have a higher risk for developing various nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 50 publications
1
34
0
1
Order By: Relevance
“…This could further explain their adaptation to rotating night shift without disturbing their circadian cycle. The correlation between circadian adjustment in shift workers and chronotype is widely supported in the literature (Hittle & Gillespie, 2018; Razavi et al., 2019). In our study, more rotating night shift nurses reported chronotype‐to‐shift alignment, adding further evidence for the adaptation of nurses to rotating night shift.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This could further explain their adaptation to rotating night shift without disturbing their circadian cycle. The correlation between circadian adjustment in shift workers and chronotype is widely supported in the literature (Hittle & Gillespie, 2018; Razavi et al., 2019). In our study, more rotating night shift nurses reported chronotype‐to‐shift alignment, adding further evidence for the adaptation of nurses to rotating night shift.…”
Section: Discussionmentioning
confidence: 75%
“…Shift work can disturb an individual's chronotype or tendency to sleep at certain times during the day; this is an important factor that influences sleep and melatonin levels among night shift workers (Hittle & Gillespie, 2018). There are two extremes of chronotype; some people are morning types and sleep early during the night whereas others are active in the evening and have a delayed sleep period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronotype has an independent effect to melatonin rhythms affected by rotating-shift work [113]. Associations between chronotype and obesity showed mixed results [114]. Of the 5 articles exploring this link, 3 found a positive association between evening chronotype shift workers and obesity, while 2 studies did not support this relationship.…”
Section: Personal Susceptibilitymentioning
confidence: 99%
“…In healthcare, shift workers operate around the clock to care for patients needing continuous care. Shift work has been associated with health and safety risks [ 2 3 ] including burnout [ 4 5 6 ], immunological effect [ 7 ], cardiovascular disease [ 7 8 ], infection [ 7 ], sleep disturbance [ 9 ], obesity [ 10 ], and even medical errors, resulting in increased patient mortality [ 11 ]. This is likely due to circadian rhythm disruption.…”
Section: Introductionmentioning
confidence: 99%